VD_FINDINFO HC / 2012 / 132 vom 9. Februar 2012 - VD Tribunal cantonal (2012)
SUSPENSION DE LA PROCÉDURE, MESURE PRÉPROVISIONNELLE, SIGNATURE, PRINCIPE DE LA CÉLÉRITÉ | 29 al. 1 Cst., 126 al. 1 CPC (CH), 130 al. 1 CPC (CH), 265 al. 2 CPC (CH)